Analyzing toxicological effects of AsIII and AsV to Chlamys farreri by integrating transcriptomic and metabolomic approaches. (January 2023) - Liu, Huan; Tian, Xiuhui; Gong, Xianghong; Han, Dianfeng; Ren, Lihua; Cui, Yanmei; Jiang, Fang; Zhao, Junqiang; Chen, Jianqiang; Jiang, Lisheng; Xu, Yingjiang; Li, Huanjun
Abstract: Inorganic arsenic (iAs) is a widespread contaminant in marine environments, which is present in two different oxidation states (arsenate (AsV) and arsenite (AsIII)) that have complex toxic effects on marine organisms. The scallop Chlamys farreri ( C. farreri ) accumulates high levels of As and is a suitable bioindicator of As. In this report, we integrated transcriptomics and metabolomics to investigate genetic and metabolite changes and functional physiological disturbances in C. farreri exposured to inorganic arsenic. Physiological indicators antioxidant factors and cell apoptosis analysis macroscopically corroborated the toxic effects of inorganic arsenic revealed by omics results. Toxic effects of inorganic arsenic on C. farreri were signaling-mediated, causing interference with a variety of cell growth and small molecule metabolism. The results provide evidence that inorganic arsenic disrupts the physiological functions of bivalves, highlighting the correlations between different metabolic pathways and providing new insights into the toxic effects of environmental pollutants on marine organisms. Graphical abstract: Unlabelled Image Highlights: The metabolism of scallops is disrupted by exposure to inorganic arsenic. Signaling-dependent toxic effects of arsenic have been tentatively elucidated. Induced metabolic pathways by inorganic arsenic are described holistically. Integrated transcriptome and metabolome analysis of inorganic arsenic toxicity.